A Platinum Cantilever-Based TCD for 3-Omega Sensing of Gas Mixtures. (23rd July 2018) - Lotfi, Ardalan; Navaei, Milad; Hesketh, Peter J
Abstract : This paper is on the fabrication and characterization of a platinum cantilever-based TCD gas sensor for detection of highly toxic and corrosive ammonia gas. The sensor is made of platinum and supported with 100nm Al2 O3 for its mechanical strength. To improve the signal to noise ratio of sensing technique, 3-Omega technique is used. The fabricated platinum cantilever-based TCD sensor successfully detect 60 ppm ammonia in helium carrier.